Masculinity, Capital, and Cultural Continuity in the Blater Community of Rural Indonesia - Dinara Maya Julijanti; Moch. Imron Rosyidi; Ach. Fawaid As'ad (ETTISAL : Journal of Communication, 2025)
This study explores the remo tradition as a ritual communication practice within the blater community of West Madura. While previous studies have largely treated remo as cultural heritage or as a sociological phenomenon, this research employs both functional theory and symbolic interactionism to reveal how the tradition simultaneously maintains social order and produces symbolic meaning. Using a phenomenological approach, data were collected through participant observation and interviews with remo performers in Bangkalan, including senior members who have been involved since the 1970s. Findings show that remo operates as a communicative system in which greetings, seating arrangements, invitations, and the public announcement of contributions function as signs that transform various forms of capital—economic, cultural, social, and symbolic—into visible recognition. Functionally, remo ensures cohesion, reciprocity, and the continuity of group order. Symbolically, it performs honor, masculinity, and solidarity, reaffirming the identity of the blater. The ritual endures not because of economic gain but because of its capacity to convert resources into symbolic prestige and long-term social networks. Despite the pressures of globalization and digital media, remo continues to persist by adapting its form while maintaining its communicative codes. This study contributes to communication and cultural studies by demonstrating how ritualized interaction sustains identity and legitimacy in local communities. It highlights that cultural continuity depends not only on preserving heritage but also on maintaining the communicative architecture through which tradition gains meaning.